Artificial water channels-embedded PVDF membranes for direct contact membrane distillation and ultrafiltration - Nursiah, Kelvinraj; Musteata, Valentina-Elena; Cerneaux, Sophie; Barboiu, Mihail (Frontiers in Membrane Science and Technology, 2023)
Innovative self-supported flat-sheet polyvinylidene fluoride (PVDF) membranes were developed incorporating amphiphilic I-quartet Artificial Water Channels (AWCs) and applied for membrane distillation (MD) and Dyes Ultrafiltration (UF). The presence of AWCs was aimed to increase the amount of water within hydrophobic PVDF pores increasing water permeability and preserving high selectivity and consequently to improve the MD and dyes UF performances. We explored novel strategies in which water channels structures contribute to water cluster stabilization and the increase of water (vapors or liquid) within hydrophobic pore structures. With this novel strategy in mind, three PVDF polymer grades with different molecular weights as well as the variation of their mass concentration as well as of AWCs were studied to shed in light their influence on the water permeability using a dead-end filtration setting. An enhanced water permeability of 75.3 L.m -2 .h -1 .bar -1 was attained for the PVDF-AWC hybrid membrane prepared using 16 wt.% PVDF (530 000 g/mol) and 0.05 wt.% AWCs when compared with a reference membrane with a water permeability of 30.6 L.m -2 .h -1 .bar -1 . The MD performances of both membranes were assessed using a 35 g/L NaCl aqueous solution to yield a salt rejection of 95.3% and 85.2%, respectively. Furthermore, both the reference and the PVDF-AWC membranes showed improved separation performance in terms of rejection efficiency and dye permeability for binary dyes mixture as compared to single dyes. Among all the tested membranes, while methylene blue was completely removed in both cases, the 14 wt.% PVDF membrane incorporating 0.075 wt.% AWC showed a methyl orange rejection efficiency of up to 99.8% compared to 98.4% for its reference membrane. This hybrid membrane also displayed an almost doubled filtered dye feed permeability of 84 L.m -2 .h -1 .bar - 1 , compared to 40 L.m -2 .h -1 .bar -1 for its 14 wt.% PVDF reference membrane.